Accounting Practice in Society : A Communicative Action Analysis - Sawarjuwono, Tjiptohadi; Gafï¬kin, Michael JR (The International Journal of Accounting and Business Society, 1994)
Habermas's theory of communicative action is a general theory of society that provides a theoretical framework for analysing social evolution. ln this theory, based on the linguistic paradigm. Habermas conceptualises that a society. Analytically, can be viewed from two aspects ofinteractions, social integration and system integration. However, the interaction does not always take place within the linguistic medium. lt may exert in other media ‘money’ and ‘power’. The process of accounting, the development of accounting theory and practice, seems to follow the social interaction. Therefore, this study argues that accounting is a product of social interaction. Accounting represents a changing product of continuously changing society. It then attempts to interpret and analyse accounting from a societal evolution point of view. lt is believed that the implementation ofthe theory ofcommunicative action promotes a rigor design to understand in depth the accounting practice problem and able to provide it with a better suggestion. Keywords: Accounting knowledge and practice, Habermas‘ Theory of Communicative Action, Indonesia.